Two-Stage Crystallization Combining Direct Succinimide Synthesis for the Recovery of Succinic Acid From Fermentation Broth - Xiao, Yiwen; Zhang, Zhibin; Wang, Ya; Gao, Boliang; Chang, Jun; Zhu, Du (Frontiers in Bioengineering and Biotechnology, 2020)
Succinic acid is an important chemical and raw material widely used in medicine, food, biodegradable materials, fine chemicals and other industrial fields. However, traditional methods for purifying succinic acid from fermentation broth are costly, poorly efficient, and harmful to the environment. In this study, an efficient method for purifying succinic acid from the fermentation broth of Escherichia coli NZN111 was developed through crystallization and cocrystallization with urea. First, the filtrate was collected by filtering the fermentation broth, and pH was adjusted to 2.0 by supplementing sulfuric acid. Crystallization was carried out at 8C for 4 h to obtain succinic acid crystals. The recovery rate and purity of succinic acid were 73.4% and over 99%, respectively. Then, urea was added to the remaining solution with a mass ratio of urea to residual succinic acid of 4:1 (murea/mSA). The second crystallization was carried out at pH 2 and 4C for 12 h to obtain succinic acid-urea cocrystal. The recovery rate of succinic acid residue was 92.0%. The succinic acid-urea crystal was further mixed with phosphorous acid (4.2% of the mass of succinic acid cocrystal) and maintained at 195C for 6 h to synthesize succinimide, and the yield was >80%. This novel and efficient purification process was characterized by the significantly reduced urea consumption, and high succinic acid recovery (totally 95%), and high succinimide synthesis yield (80%). Thus, this study potentially provided a novel and efficient strategy for the industrial production of succinic acid and succinimide.